Clinical utility of target-based next-generation sequencing for drug-resistant TB - Mansoor, H; Hirani, N; Chavan, V; Das, M; Sharma, J; Bharati, M; Oswal, V; Iyer, A; Morales, M; Joshi, A; Ferlazzo, G; Isaakidis, P; et al. (The international journal of tuberculosis and lung disease, 2023)
In high TB burden countries, access to drug susceptibility testing is a major bottleneck. Targeted next-generation sequencing (tNGS) is a promising technology for rapid resistance detection. This study assessed the role of tNGS for the diagnosis of drug-resistant TB (DR-TB). A total of 161 samples from bacteriologically confirmed TB cases were subjected to tNGS using the Deeplex Myc-TB kit and sequenced using the MiSeq platform. These samples were also processed for conventional phenotypic DST (pDST) using 13 drugs on Mycobacteria Growth Indicator Tube and line-probe assays (MTBDR and MTBDR ). There were 146 DR-TB and 15 drug-susceptible TB (DS-TB) samples. About 70% of patients with DR-TB had no previous TB treatment history. Overall, 88.2% had rifampicin-resistant/multidrug-resistant TB (RR/MDR-TB), 58.5% pre-extensively drug-resistant TB (pre-XDR-TB) and 9.2% had XDR-TB as defined by the WHO (2020). Around 8% ( = 13) of samples were non-culturable; however, identified 8 were resistant to first and second-line drugs using tNGS. Resistance frequency was similar across methods, with discordance in drugs less reliable using pDST or with limited mutational representation within databases. Sensitivities were aligned with literature reports for most drugs. We observed 10% heteroresistance, while 75% of strains were of Lineages 2 and 3. Programme data supported tNGS in the diagnosis of DR-TB for early treatment using individualised regimens.